2014
DOI: 10.1371/journal.pone.0100153
|View full text |Cite|
|
Sign up to set email alerts
|

The Relationship between Therapeutic Alliance and Service User Satisfaction in Mental Health Inpatient Wards and Crisis House Alternatives: A Cross-Sectional Study

Abstract: BackgroundPoor service user experiences are often reported on mental health inpatient wards. Crisis houses are an alternative, but evidence is limited. This paper investigates therapeutic alliances in acute wards and crisis houses, exploring how far stronger therapeutic alliance may underlie greater client satisfaction in crisis houses.Methods and FindingsMixed methods were used. In the quantitative component, 108 crisis house and 247 acute ward service users responded to measures of satisfaction, therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 36 publications
(48 reference statements)
4
53
0
7
Order By: Relevance
“…The qualitative papers generally scored well for reporting the analysis used, but there was little or no acknowledgement of the impact of the researcher on the research process. The four mixed methods papers scored 0% (Lovell, 1995), 25% (Sweeney et al, 2014), 50% (Greenwood et al, 1999) and 75% (Ricketts, 1996) respectively.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The qualitative papers generally scored well for reporting the analysis used, but there was little or no acknowledgement of the impact of the researcher on the research process. The four mixed methods papers scored 0% (Lovell, 1995), 25% (Sweeney et al, 2014), 50% (Greenwood et al, 1999) and 75% (Ricketts, 1996) respectively.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Five studies (Greenwood et al, 1999;Kohler et al, 2015;Ricketts, 1996;Smith et al, 2014;Sweeney et al, 2014) reported a mean score of the Client Satisfaction Questionnaire (CSQ-8/ZUF-8), with scores ranging from 21 to 26.8 (mean score 23.53). The CSQ-8 consists of a range of potential scores from 8 to 32, with higher scores indicating greater satisfaction.…”
Section: General Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was acknowledgement that, while retaining moral and ethical responsibility, peer workers in peer-led organisations were not bound by the same legal duty of care as a statutory service provider and as such were able to work more flexibly, enabling service users to own their own risks as part of a therapeutic process (Morgan 2000). It has been suggested that encouraging a personal sense of autonomy in this way is not only of therapeutic value in its own right but supports a virtuous circle of improved relationships between staff and service users (Sweeney et al 2014).…”
Section: Risk Management Risk Adversity and Responsibilitymentioning
confidence: 99%
“…In the context of mental health care, dissatisfaction with care received has been found to be associated with adverse outcomes: lack of service uptake, poor therapeutic alliance, discontinuation of care, a higher number of unmet needs and lower quality of life [711]. However, consistently high levels of satisfaction reported in studies have prompted researchers to warn that caution needs to be exercised in the interpretation of results [12].…”
Section: Introductionmentioning
confidence: 99%